Development of mobile incubator for quail egg productions in Malaysia / Fatimah Nur Mohd Redzwan, Nur Idawati Md. Enzai and Mazratul Firdaus Mohd Zin - Mohd Redzwan, Fatimah Nur; Md. Enzai, Nur Idawati; Mohd Zin, Mazratul Firdaus (2017)
The purpose of this project is to design and develop the system of a forced-air egg incubator that is able to incubate quail bird, which is called Mobile Quail Egg Incubator System (MQEIS). The main usage of MQEIS is to incubate quail eggs for quail production in Malaysia. This incubator is equipped with temperature and humidity sensor that could measure the condition of the quail egg. Inaccurate control of the incubator could affect the temperature and humidity of the incubator to become higher or lower. In this project, a small bulb is located inside the incubator to provide suitable temperature for the quail eggs. In order to maintain the good condition of humidity and ventilation, the incubator is filled up with small amount of water and controlling fan works as the cooling element to regulate air inside the incubator for the hatching process. The LCD screen display, which is located at the front of incubator machine, will display status condition of the incubator in term of its temperature and humidity. The whole incubator system is controlled by the ArduinoAtMega328p as the mainmicrocontroller. This Arduino microcontroller is programmed to produce the desired output. The humidity sensor (DHT11) is connected to Arduino to detect humidity and temperature, which then will be displayed digitally on 16 x 2 LCD screen. The digital controller (W1209) is then used to control the heating element. The processed data from sensors is simulated by the digital thermostat (W1209) and will be executed by the control element to change the condition of the bulb either turning it on or off. The incubator machine has been tested and achieved suitable temperature and humidity of 38℃ and 64% respectively. The prototype of this MQEIS is made from Styrofoam polystyrene due to its light-weight and compact size.